NEO-GLS: Innovating School Literacy with Read Aloud and DEAR for Indonesian Students - Putra, Ikhza Mahendra; Dari, Mika Wulan; Wartiningsih, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This study examines the innovation of NEO-GLS (New Evolution of School Literacy Movement), Gerakan Literasi Sekolah (GLS) development aimed at improving literacy among Indonesian students. NEO-GLS is an evolution of the previous national literacy program, offering a more structured and interactive approach to addressing 21st-century literacy challenges. In response to data highlighting low literacy rates, NEO-GLS aims to create an inclusive and interactive literacy environment that fosters both academic growth and social engagement. The program integrates two key innovative methods: Read Aloud and Drop Everything and Read (DEAR). These methods are designed to enhance students' reading skills and encourage interest, motivation, and active participation in the learning process. By incorporating enjoyable and engaging reading activities, the program helps develop students"™ critical thinking skills while promoting a lifelong love for reading. This study employs a conceptual qualitative approach to investigate the program's concept and impact. Through structured stages of habituation, development, and learning, NEOGLS aims to improve students' text comprehension and vocabulary acquisition significantly. Continuous evaluation, teacher support, and collaboration with key stakeholders, including parents and educators, are essential for ensuring the successful implementation of NEO-GLS. The findings are expected to promote self-directed learning and equip students with the skills needed to navigate an increasingly complex and dynamic global landscape